MODEL PEMBELAJARAN LANGSUNG TERHADAP KETERAMPILAN MENYETEK SISWA TUNARUNGU KELAS VI DI SLB B - MARTHA NENDY, ANCHA (Jurnal Pendidikan Khusus, 2016)
ABSTRACT Deaf students are unable to hear. They use their sense of vision sight to obtain information. To do this, they rely on a visual learning. The cutting ability of deaf students can be optimally developed as they have potential in doing visual tasks. Direct instruction model is a teaching approach which is able to help deaf students study the basic skills and obtain information based on the structured procedure. This research aims to determine the effect of direct instruction model on the ability of deaf students to cutting in class VI SLB B Karya Mulya Surabaya. The results of data analysis by Wilcoxon Match Pairs Test are Zobserved (Zh) = 2.20 with  Ztables 5%= 1.96, as Zh> Ztable is 2.20 larger than 1.96. It means that there is a significant influence of the direct instruction model on the ability of deaf students to cut in class VI SLB B Karya Mulya Surabaya. Keywords: Direct instruction model, the ability of deaf students to cutting